2017
DOI: 10.1128/jvi.01718-16
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus LMP1-Mediated Oncogenicity

Abstract: Epstein-Barr virus latent membrane protein 1 (LMP1) is expressed in multiple human malignancies, including nasopharyngeal carcinoma and Hodgkin and immunosuppression-associated lymphomas. LMP1 mimics CD40 signaling to activate multiple growth and survival pathways, in particular, NF-B. LMP1 has critical roles in Epstein-Barr virus (EBV)-driven B-cell transformation, and its expression causes fatal lymphoproliferative disease in immunosuppressed mice. Here, we review recent developments in studies of LMP1 signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 85 publications
1
107
0
1
Order By: Relevance
“…LMP1, as an EBV-encoded viral antigen, is a kind of oncogenic gene and participates in the activation of signaling pathways such as NF-κB, JNK-p38/SAPK, Ras-MAPK, PI3k-Akt and JAK-STAT, which can promote the occurrence of EMT and make nasopharyngeal carcinoma has a higher invasion and metastasis ability, which is considered to be an important factor in the development of nasopharyngeal carcinoma [42]. Studies have found that EBV-miR-BART9, EBV-miR-BART16 and EBV-miR-BART17-5p can both target the 3'UTR of LMP1 mRNA and negatively regulate the expression of LMP1.…”
Section: Antigen Expressionmentioning
confidence: 99%
“…LMP1, as an EBV-encoded viral antigen, is a kind of oncogenic gene and participates in the activation of signaling pathways such as NF-κB, JNK-p38/SAPK, Ras-MAPK, PI3k-Akt and JAK-STAT, which can promote the occurrence of EMT and make nasopharyngeal carcinoma has a higher invasion and metastasis ability, which is considered to be an important factor in the development of nasopharyngeal carcinoma [42]. Studies have found that EBV-miR-BART9, EBV-miR-BART16 and EBV-miR-BART17-5p can both target the 3'UTR of LMP1 mRNA and negatively regulate the expression of LMP1.…”
Section: Antigen Expressionmentioning
confidence: 99%
“…The EBV latent membrane protein 1 (LMP1) is a latent oncogenic protein encoded by EBV. Studies show that LMP1 harbors the oncogenic potential through NF‐κB signaling pathway and contributes to the viral life cycle in differentiating epithelia …”
Section: Introductionmentioning
confidence: 99%
“…MiR-BART15 is capable of targeting nucleotide-bound oligomerization domain-like receptor family pyridine domaincontaining 3 (NLRP3) with less in ammation to limit in ammation and promote EBV infection [18]. LMP1 is a transmembrane latent protein encoded by EBV, which is essential for cell proliferation and transformation [19], but overexpression of LMP1 will inhibite cell proliferation, and increase the sensitivity of cells to pro-apoptotic stress [20]. According to previous reports, miR-BART19-5p can inhibit the expression of LMP1, thereby maintaining a balance between the growth-promoting effect of LMP1 and its pro-apoptotic function [10].…”
Section: Discussionmentioning
confidence: 99%